Compensation for the Victims of the Halabja Genocide in the Perspective of International and Iraqi Law - Awara Hussein Ahmed; Jamal Mohammed Ameen; Rebar Akram Faiq (JUSTICES: Journal of Law, 2025)
Genocide is an international crime that consequently has punitive, material, and moral consequences. The families of the victims must receive material, spiritual, and symbolic compensation in addition to punishing the perpetrators. International law and the national laws of Iraq and the Kurdistan Region enshrine this. Both domestic laws and transitional justice initiatives influence the judicial system in Iraq. Halabja and other crimes perpetrated by the former administration have been recognised by post-2003 legal changes, including as the creation of the Iraqi High Tribunal. Nevertheless, issues still exist, including poor compensation plan execution, a dearth of thorough legislative frameworks for reparations, and political and financial obstacles that impede the administration of justice. In this research, the method of case study and legal analysis is used to analyse the compensation of the victims of chemical attacks and genocide in Halabja. The study aims to explain the provisions and methods for genocide victims in international and Iraqi laws. In this respect, although the Iraqi High Criminal Court's recognition of the genocide in Halabja city. However, due to financial and legal problems, the law has not been implemented, and the victims of the Halabja genocide have not been compensated. In the end, offering adequate compensation is a step towards healing and reconciliation for the impacted communities as well as a matter of justice.